Poverty and the Curse of Natural Resources in Indonesia - Vellayati Hajad; Ikhsan Ikhsan; Herizal Herizal; Ikhwan Rahmatika Latif; Nodi Marefanda (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2023)
This study aims to determine how a country's abundant natural resource wealth can be utilised to bolster its economy and alleviate poverty. This study focuses on the use of natural resources to expedite development. This investigation makes use of a library-based qualitative research strategy. Data was gathered by conducting a Scopus search for natural resources-related journal articles using titles, keywords, and abstracts as metadata search references, and then analysing the results with the VOSviewer tool. We used VOSviewer to determine how many articles had been published on natural resources and discovered that a country's natural resources exceed its economic development. The purpose of utilising VOSviewer is to use it as a resource to conduct precise content analysis based on the researcher's name, publication year, researcher productivity, and natural resource research trends. This analysis was conducted for the purpose of examining the author's collaboration in the natural resources and poverty fields. The results indicate that natural resource-rich regions do not guarantee increased economic growth or reductions in poverty. Poverty in Indonesia is a complex issue, despite the fact that a number of developing nations have been successful in implementing improvements in national production and income and in reflecting the level of well-being among the country's population. The conclusion demonstrates that the resource curse in Indonesia is a result of poor resource management, which causes poverty. The influence of the resource curse on government social spending emphasises the significance of government accountability and transparency in relation to natural resource wealth.